Pharmacological Sciences: Perspectives for Research and Therapy in the Late 1990s - Cuello, A. Claudio; Collier, Brian (Birkhäuser Basel, 1995)
This volume arose from the scientific program of the XIIth International Congress of Pharmacology, held in Montreal, Canada, July 24-29, 1994. The scientific program included plenary lectures and symposia, in addition to poster presentations and colloquia. The abstracts of the Congress presentations were published as .supplement 1 of volume 72 by the Cana dian Journal of Physiology & Pharmacology. The Congress organizers sought a more expansive treatment of the Congress proceedings and appointed Dr. A. Claudio Cuello to coordinate preparation of the present volume; Dr. Brian Collier was chair of the scientific program committee and, thus, also collaborated on this work. The objective that we pursued was to produce a volume of reasonable size which would feature all of the plenary lectures and symposia from those authors who agreed to participate. To this end, we solicited mini reviews from plenary lecturers and asked symposia organizers to coordi nate a single short-review covering the individual topics within their event. Those who accepted this challenge are evident in this volume. We express our gratitude to these authors for doing so, and for exercising considerable ingenuity in completing their task within a reasonable time